Septin4 Prevents PDGF-BB-induced HAVSMC Phenotypic Transformation, Proliferation and Migration by Promoting SIRT1-STAT3 Deacetylation and Dephosphorylation - Zhang, Naijin (Int J Biol Sci, 2020)
SIRT1 and STAT3 are key to human aortic vascular smooth muscle cells (HAVSMCs) proliferation, migration and phenotypic transformation, but the regulatory mechanism of SIRT1-STAT3 in this process is still unclear. Septin4 is a cytoskeleton-related protein that regulates oxidative stress-vascular endothelial injury. However, the role and underlying mechanism of Septin4 in atherosclerosis remains unknown. Here, we revealed the role and mechanism of Septin4 in regulating SIRT1-STAT3 in atherosclerosis. We determined that the expression of Septin4 were markedly increased in Apoe(-/-) atherosclerosis mice and PDGF-BB-induced HAVSMCs. Knockdown of Septin4 significantly increased PDGF-BB-induced HAVSMCs proliferation, migration and phenotypic transformation, while overexpression of Septin4 had the opposite effects. Mechanically, co-immunoprecipitation results demonstrated that Septin4 was a novel interacting protein of STAT3 and SIRT1. Septin4 formed a complex with SIRT1-STAT3, enhancing the interaction between SIRT1 and STAT3, ensuing promoting SIRT1-regulated STAT3-K685 deacetylation and STAT3-Y705 dephosphorylation, which inhibited PDGF-BB-induced HAVSMCs proliferation, migration and phenotype transformation. Therefore, our findings provide novel insights into the prevention and treatment of atherosclerosis.